Production of diacylglycerol from palm olein using enzymatic glycerolysis and its recovery - Yeoh, Chiou Moi (2010)
Diacylglycerol (DAG) is one of the minor components that is available in edible oils and fats. DAG has novel nutritional function in suppressing the serum triacylglycerol (TAG). Enzymatic reaction is preferred over chemical reaction as it usually requires mild operating condition. Among the available enzymatic reaction, glycerolysis is selected as the reaction process since abundant supply of glycerol (GLY) is expected from the biodiesel industry. The common edible oil that is available in Malaysian market, palm olein, is selected as the raw material for the reaction. The main objective of this study was to produce in a cost effective way of edible oil of at least 80 wt-% of DAG purity and less than 0.1 wt-% of free fatty acid (FFA). The research began with the screening a few commercial enzymes. After consideration of the enzyme cost, Lipozyme TL IMTM was selected as the catalyst for the glycerolysis reaction. The operating parameters affecting the reaction were studied in order to optimize the DAG yield. Introduction of silica gel as additional solid support for the GLY significantly enhanced the reaction. However, the tocolpherols and tocotrienols (tocols) content in the oil were reduced. The optimum temperature for the glycerolysis reaction was 55 C. As the addition of silica gel reduced the tocols content, the glycerolysis reaction was conducted without the presence of the silica gel. In this approach, the glycerol-enzyme (G/E) mass ratio was greatly affecting the reaction yield. The optimum G/E mass ratio was found to be ranged between 0.8 and 1.5. The mass ratio below 0.8 and above 1.5 was not recommended for the reaction as the reaction is either slow or inhibited. It was found that increasing of the enzyme load could shorten the reaction time. Kinetic study of the glycerolysis reaction was developed based on the Michaelis-Menten mechanism. Three models were studied which were simple ternary model,simple ping-pong bi bi model, and complex ping-pong bi bi model. Among these models, the complex ping-pong bi bi model was the most appropriate model to describe the glycerolysis reaction. DAG purity in the product was increased by purification using short-path distillation (SPD). Besides increasing the DAG purity, the FFA content in the product was also need reduced below 0.1 wt-%. A single-stage purification process was not able to increase the DAG purity to above 80 wt-%. Double-stage purification process was recommended as it could increase the DAG purity to above 80 wt-%. It was found that the removal of TAG at the first stage and the removal of the FFA at the second stage was able to achieve 89.9 wt-% of DAG purity without exceeding the limit of 0.1 wt-% of FFA. A detailed DAG profile was identified and other product characterization such as fatty acid composition (FAC), slip melting point (SMP), and solid fat content (SFC) profile were also carried out. It was found that high DAG product had lower iodine value (IV) and higher SMP than raw material palm olein. The tocols content in the high DAG product was 1134 ppm.